The pancreas an integrated textbook of basic science, medicine, and surgery - Beger, Hans G. 1936-; Büchler, Markus W. 1955-; Hruban, Ralph H.; Mayerle, Julia 1973-; Neoptolemos, John P.; Shimosegawa, Tooru; Warshaw, Andrew L. 1939-; Whitcomb, David C.; Zhao, Yupei (Wiley Blackwell, 2023)
The PANCREASThe newest edition of the essential guide to pancreatic medicineThe fourth edition of The Pancreas: An Integrated Textbook of Basic Science, Medicine and Surgery integrates the cutting-edge research of recent years to update its presentation of this fast-growing subject. It details every known disorder of the pancreas, grounding them in a thorough understanding of pancreatic function, enhanced with high quality illustration and graphs. It also includes step-by-step guidance for relevant endoscopic techniques and surgical procedures.The Pancreas readers will also find:* New comprehensive insights into three pancreatic diseases: autoimmune pancreatitis, cystic neoplasms, and neuroendocrine tumors* An editorial team with decades of clinical and research experience in the US, Europe, and Asia* Over 500 downloadable illustrations for use in scientific presentationsThe Pancreas is a foundational reference for clinicians and researchers in gastroenterology and gastrointestinal surgery.